Creation of 4-Quinolone Thioether and Selenoether Derivatives via Pd-NHC Catalysed Cross-Coupling Reaction - Ghosh, Prasanjit; Das, Sajal (SynOpen, 2020)
Pd-NHC catalysed direct sulfenylation and selenylation of 3-iodo-4-quinolones has been developed. This protocol provides an alternative route for the construction of ipso-C–S and C–Se bond formation in 4-quinolones under aerobic conditions.
Keywords: 4-quinolone; Pd-NHC; sulfenylation; selenylation; cross-coupling